Environmental and Agricultural Informatics 2020
DOI: 10.4018/978-1-5225-9621-9.ch004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Kisan Call Centers on the Farming Sector

Abstract: The Indian Agriculture has been an area with varied challenges. This sector is responsible for the growth rate and generating a per capita income. This sector generates a whopping 28% of the total GDP of India and over 15% of the total exports. The usage of Internet and phone technology can fill these gaps to a large extent. A continuous two way interaction among the farmers and agricultural scientists will ensure agricultural extension. A landmark step was taken on January 21, 2004 when the Department of Agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2004, the Indian government started a program to provide telephonic help to the countrywide farmers in their local language on the toll-free number "1800-180-1551". Moreover, many studies have shown the program's positive outcomes in farmers' livelihood and economic conditions over the years ( [3], [4], [5]).…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, the Indian government started a program to provide telephonic help to the countrywide farmers in their local language on the toll-free number "1800-180-1551". Moreover, many studies have shown the program's positive outcomes in farmers' livelihood and economic conditions over the years ( [3], [4], [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, it has become a cornerstone of agricultural assistance, offering farmers a platform to seek guidance, information, and solutions to their pressing agricultural concerns (Godara & Toshniwal, 2020;. The KCC, operated by the Punjab government, records and manages an extensive dataset of farmer query calls, encompassing various topics, from crop cultivation techniques to pest management strategies and government schemes (Chachra et al 2020; Kaur et al 2020).…”
Section: Introductionmentioning
confidence: 99%